(untitled) (Research, Society and Development, 2020)
In this study, recycled medium from three photosynthetic microorganisms (Chlorella vulgaris, Dunaliella tertiolecta and Arthrospira platensis) was evaluated for use in producing β-galactosidase, an enzyme traditionally used to degrade lactose in dairy products. Recycled medium from Chlorella vulgaris was selected to optimize culture medium to be used to produce β-galactosidase by Enterococcus faecium in submerged fermentation. Response Surface Methodology (RSM) was used to optimize the levels of the variables: temperature (30-40°C), lactose concentration (0-5%), fermentation time (12-24h), pH (6-8) and their interaction. All variables studied had a statistically significant effect on the production of β-galactosidase. The optimal conditions for producing the enzyme were achieved: temperature of 31ºC, lactose concentration of 5.34%, fermentation time of 12h and pH of 8.0. Under these conditions, the β-galactosidase activity was 29.85 U/mL which was quite close to the predicted value (30.83 U/mL). Finally, it can be concluded that recycled medium from optimized C. vulgaris supernatant may well be important for the biotechnology industry as it is an abundant low-cost source for producing β-galactosidase by Enterococcus faecium.